Billion dollar cowboy ebook - Brown, Carolyn (Cowboys & Brides, 2013)
Book 1 of Cowboys & Brides From New York Times and USA Today-bestselling author Carolyn Brown comes a contemporary Western romance filled to the brim with sexy cowboys, gutsy heroines, and genuine down-home Texas twang. Colton Nelson was twenty-eight years old when he won the Texas Lottery and went from ranch hand to ranch owner overnight. Now he's desperate to keep the gold diggers away. It shouldn't be too hard to find a pretty girl and hire her to pretend to be his one-and-only. Laura Baker's got mixed feelings about this—she's on the ranch to work, not to be arm candy. On the other hand, being stuck for a while in the boondocks with a gorgeous cowboy isn't half-bad. What neither Colton nor Laura expects are the intensely hard lessons they have to learn about the real cost of love... Fans of Linda Lael Miller and Diana Palmer will thrill to this moving story of a marriage of convenience between a cowboy who has it all...and the woman he could never have enough of. Cowboys & Brides Series: Billion Dollar Cowboy (Book 1) The Cowboy's Christmas Baby (Book 2) The Cowboy's Mail Order Bride (Book 3) How to Marry a Cowboy (Book 4) Praise for Bestselling Contemporary Western Romances by Carolyn Brown: "An old-fashioned love story told well... A delight."—RT Book Reviews, 4 Stars "Sizzling hot and absolutely delectable."—Romance Junkies "Funny, frank, and full of heart... One more welcome example of Brown's Texas-size talent for storytelling."—USA Today Happy Ever After "Alive with humor... Another page-turning joy of a book by an engaging author."—Fresh Fiction